Abordagem numérica da teoria quântica de circuitos - Silva, José Jaédson Barros da (2015)
One of the devices most important in mesoscopic physics is the quantum dot. This device consists of a cavity of submicrometrics dimensions formed in the interface plane of a electron gas two-dimensional (2DEG) in a semiconductor heterostructure, wherein is possible to study the properties of electronic transport coupling to the two reservoirs and establishing an electric current in the system. In this dissertation we studied the quantum theory of circuits by means of numerical methods with the goal to calculate the observables of transport, such as the conductance and the shot-noise power in a single quantum dot and in two quantum dots coupled in series. In a quantum dot was implemented the numerical method of bisection in Fortran to find the pseudocurrent and, through this, to calculate the conductance and the shotnoise power in a symmetric quantum dot and also in a assymmetric quantum dot. In the case of a symmetric dot were compared the numerical results obtained by bisection method with the analytical results found in the literature and was shown that there is a perfect agreement. We also implemented Newton’s method for two quantum dots associated in series and we calculate the conductance and the shot-noise power. The numerical results obtained by the Newton’s method, for two symmetric quantum dots in series, were also compared with the analytical results founds in the literature and showed excellent agreement.